2017
DOI: 10.1287/mnsc.2016.2467
|View full text |Cite
|
Sign up to set email alerts
|

Behavior-Based Pricing in Vertically Differentiated Industries

Abstract: We study behavior-based pricing (BBP) in a vertically differentiated model. Vertical differentiation is innately asymmetric because all customers prefer the higher-quality product when prices are equal. This asymmetry causes BBP to have different properties than symmetric horizontally differentiated models. We highlight two dimensions that affect the analysis: the role of quality-adjusted cost differences between the firms and the role of consumer discounting relative to firm discounting. In the second period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…The traditional products and green product indexed j ∈ (T1, T2, G), are located at three ends of the triple Hotelling line as shown in Figure 1., respectively. Following Kuksov and Lin [39], Rhee and Thomadsen [40], and Jing [41], we assume consumers derive a base value V j = v b + ρv from the product j, where v b ≥ 0 is a constant that represents basic utility to all consumers when the product meets the minimum quality standard v. In other words, v b captures the reservation value of a consumer who does not need more than a basic product of minimal quality. v ∈ [ v, +∞) defines the product quality and valuation where ρ ∈ (0, 1] is a scale factor that reflects consumers' attitudes to green products.…”
Section: Firmsmentioning
confidence: 99%
“…The traditional products and green product indexed j ∈ (T1, T2, G), are located at three ends of the triple Hotelling line as shown in Figure 1., respectively. Following Kuksov and Lin [39], Rhee and Thomadsen [40], and Jing [41], we assume consumers derive a base value V j = v b + ρv from the product j, where v b ≥ 0 is a constant that represents basic utility to all consumers when the product meets the minimum quality standard v. In other words, v b captures the reservation value of a consumer who does not need more than a basic product of minimal quality. v ∈ [ v, +∞) defines the product quality and valuation where ρ ∈ (0, 1] is a scale factor that reflects consumers' attitudes to green products.…”
Section: Firmsmentioning
confidence: 99%
“…Zhang (2011) further shows that when firms customize the horizontal attributes of products, profits become even lower than when firms only practice BBP. Research has also found some contexts in which firms can profit from BBP, such as when consumers have heterogeneous demand and preferences change over time (Shin and Sudhir 2010), asymmetric firms determine product quality (Jing 2017), consumers care about price fairness (Li and Jain 2016), competing products are vertically differentiated (Rhee and Thomadsen 2017), both manufacturers and retailers use BBP (Li 2018), or consumers are sufficiently averse to loss on match quality (Amaldoss and He 2019).…”
Section: Related Literaturementioning
confidence: 99%
“…Acquiring such information makes it feasible for enterprises to set behavior-based pricing [6]; enterprises divide consumers into "loyal customers" and "poaching customers" [7]. For "loyal customers" and "poaching customers", the enterprise will implement different degrees of premium or discount as per their historical purchase information [8,9]. There are many factors that affect the pricing of enterprise behavior.…”
Section: Literature Reviewmentioning
confidence: 99%